2013
DOI: 10.4314/ahs.v13i3.48
|View full text |Cite
|
Sign up to set email alerts
|

A report of three cases of jaundice with thyrotoxicosis

Abstract: Background: Jaundice and hepatic dysfunction have been reported in patients with thyrotoxicosis and could be due to different mechanisms. Objective: To describe three cases of jaundice occurring in patients with thyrotoxicosis and to illustrate the importance of early institution of thionamides when indicated. Methods: We present the clinical and laboratory features of three patients presenting within a year with thyrotoxicosis and jaundice and whose clinical conditions improved remarkably following treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
1
Order By: Relevance
“…Other options that have been successfully used in cases of antithyroid-induced hepatotoxicity include substituting antithyroid agents, use of cholestyramine and radioiodine. 29 Three patients in our study had antithyroid drug benzylthiouracil prior to radical approach, which consisted of radioactive iodine and total thyroidectomy. The metabolic process of 131I usually does not cause radiation damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Other options that have been successfully used in cases of antithyroid-induced hepatotoxicity include substituting antithyroid agents, use of cholestyramine and radioiodine. 29 Three patients in our study had antithyroid drug benzylthiouracil prior to radical approach, which consisted of radioactive iodine and total thyroidectomy. The metabolic process of 131I usually does not cause radiation damage to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pattern of biochemical hepatic abnormalities and hepatic injury in the setting of hyperthyroidism is variable in character and severity, it appears to be predominantly hepatitic, with a few case reports demonstrating a cholestatic pattern . The first report of hepatic necrosis in a patient with thyrotoxicosis occurred in 1874 .…”
Section: Introductionmentioning
confidence: 99%
“…Further studies demonstrated that the degree of biochemical hyperthyroxinaemia does not correlate with cellular and ultrastructural abnormalities . Liver abnormalities were mostly hepatitic with predominantly serum aspartate transaminotransferase (AST), alanine aminotransferase (ALT), and bilirubin elevations, with some increased serum alkaline phosphatase (AP) and gamma‐glutamyltransferase (GGT) concentrations . However, AP elevations may not necessarily originate from the liver and can represent elevations in the bone isoenzyme .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally we have case reports on medication errors in anesthetic practice 46 ; vitamin B12 deficiency presenting with acute confusion 47 ; and cases of jaundice with thyrotoxicosis. 48 It is high time communicable diseases received the attention they deserve in the context of infections and dysfunctional health systems in LMICs.…”
Section: Editorialmentioning
confidence: 99%